2017
DOI: 10.1089/pho.2016.4249
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a 940 nm Diode Laser with Radial Firing Tip and Bare End Fiber Tip onEnterococcus faecalisin the Root Canal Wall Dentin of Bovine Teeth: AnIn VitroStudy

Abstract: Within the studied parameters, 940 nm diode laser in conjugation with RFT showed a satisfactory bactericidal effect without any thermal side effect to the tooth-supporting tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Slight agitation of dye solution will eliminate any trapped air and contact with bacteria will be more predictable [12]. For enhanced effects a radial firing tip with optimum emission pattern of light should be used [54]. This will also result in even distribution of light and eradication of bacteria up to a depth of 1mm ensuring effective disinfection of root canal system even in cases of persistent infection where microbes like E. faecalis may penetrate up to a depth of 150 µm [55,56].…”
Section: Methods Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…Slight agitation of dye solution will eliminate any trapped air and contact with bacteria will be more predictable [12]. For enhanced effects a radial firing tip with optimum emission pattern of light should be used [54]. This will also result in even distribution of light and eradication of bacteria up to a depth of 1mm ensuring effective disinfection of root canal system even in cases of persistent infection where microbes like E. faecalis may penetrate up to a depth of 150 µm [55,56].…”
Section: Methods Of Usementioning
confidence: 99%
“…It is also found that use of optical fiber for addition of aPDT within the root canal system is better than application of laser light directed at access cavity [53]. In a recent study, radial firing tip is found to be superior method of application of aPDT and significantly more viable E. faecalis were removed within the prepared root canals when compared to bare end fiber tips [54]. In a recent study Kasic S. et …”
Section: Apdt In Endodonticsmentioning
confidence: 98%
“…[17][18][19] Diode lasers (810, 940 and 980 µm wavelengths) display huge water transmission, reaching the bacteria in deeper layers of dentinal tubules in result. 20 Schulte-Lunzum et al 21 demonstrated that 940 nm diode laser has an intensely high bactericidal effect on Enterococcus faecalis which is the most isolated microorganism in failing endodontic cases, even at the 1000 µm depth of dentinal tubules.…”
Section: Introductionmentioning
confidence: 99%
“…Since diode laser does not damage the dental hard tissues, it is effective on microorganisms in dentinal tubules (de Souza et al, 2008). A study showed that diode laser irradiation provides has high bactericidal effect against Enterococcus faecalis, the bacteria that are the most difficult to eliminate, even at the 1000-μm depth of dentine (Schulte-Lunzum et al, 2017).…”
Section: Introductionmentioning
confidence: 99%